Fundamentals of Electric Circuits - Alexander, Charles K. and Sadiku, Matthew N. O. (New Dehli, India McGraw-Hill Education Private Limited, 2013)
Aims to present circuit analysis in an easier to understand manner. Here, students are introduced to the six-step problem-solving methodology, and are consistently made to apply and practice these steps in practice problems and homework problems, using the KCIDE for Circuits software.
Include Appendices, Index and Illustrations.
Keywords: Electric Circuits